2018
DOI: 10.17221/76/2017-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of unintended 1/96 infectious bronchitis vaccine transmission in broilers after direct contact with vaccinated ones

Abstract: Infectious bronchitis virus is characterised by an extreme degree of variability which deeply affects the first-choice control strategies against the disease. Each country tends to adopt its own protocols and even vaccine producers themselves can also adopt different strategies in attempts to confront local epidemiological concerns. In the present study, we tested the potential environmental persistence, transmission ability and replication capability of a non-directly administrated vaccine strain at a hatcher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
3
2
0
Order By: Relevance
“…A high IBV GC load was detected in dust samples and tracheal swabs at 10 dpv with a subsequent decline in the detection rates and GC load in individual birds at 17 and 24 dpv, followed by increase in GC load at 31 dpv. This profile is in agreement with previous studies that reported vaccine virus shedding from 3 dpv, and a peak in viral load and detection rates at 11 and 14 dpv [ 13 , 14 , 37 ]. Later increase in the viral load could be due to re-excretion of the virus from persisting infection.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A high IBV GC load was detected in dust samples and tracheal swabs at 10 dpv with a subsequent decline in the detection rates and GC load in individual birds at 17 and 24 dpv, followed by increase in GC load at 31 dpv. This profile is in agreement with previous studies that reported vaccine virus shedding from 3 dpv, and a peak in viral load and detection rates at 11 and 14 dpv [ 13 , 14 , 37 ]. Later increase in the viral load could be due to re-excretion of the virus from persisting infection.…”
Section: Discussionsupporting
confidence: 93%
“…Vaccine and field strains of IBV and NDV have been detected in tracheal, oropharyngeal or choanal cleft swabs for variable lengths of time post infection or vaccination. Different strains of IBV were detected in tracheal tissue [ 12 ], and tracheal [ 13 17 ], choanal cleft [ 13 , 18 , 19 ] and oropharyngeal swabs [ 20 ]. Similarly, NDV RNA has been detected from oral [ 21 ], oropharyngeal [ 22 , 23 ] and tracheal [ 24 ] swabs.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, 89.3% of the detected vaccine-derived strains were 4/91-like ones. In all 72.8% of the 4/91 detections occurred in farms not adopting this vaccine, as opposed to 6.4% and none of the 1/96 and CR88 detections: the significant difference ( P -value < 0.001) suggests a higher spreading capability of the 4/91 vaccine compared to the 1/96-based one, as previously reported (Franzo et al., 2014; Pellattiero et al., 2018). Several causes could justify the observed scenario, including a higher vaccine shedding or longer persistence.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, IBV vaccine kinetics has been previously described in field and experimental conditions [36,40] that supported the suitability of the group size and trial duration for the vaccine circulation and detection, allowing also to compare the herein obtained results with an expected trend of viral replication.…”
Section: Discussionsupporting
confidence: 70%